JANTUNG PISANG TERHADAP PENINGKATAN PRODUKSI ASI DI DESA SUNGAI PUTIH TAHUN 2018 - RICE NOVIAWANTI; Lidia Fitri; Inda Ika Silalahi (STIKes Al-Insyirah Pekanbaru, 2019)
Breast milk is the best baby food that is rich in antibodies, useful for endurance and antibiotics in high numbers so that exclusive breastfeeding can reduce the risk of death. The percentage of 0-5 months babies in Indonesia who get exclusive breastfeeding is only 54.0%, while infants up to 6 months of age are only 29.5%. The preliminary survey data in Sungai Putih Village found that 4 out of 74 mothers did not give breast milk on the grounds that they bothered 1 person and the milk was not smooth 3 people. The aim of the study was to determine the relationship of the banana blossom to the production of breast milk. This type of research is quantitative analysis with a pre-experimental method with a one group pretest posttest approach. The population is nursing mothers with a baby age range> 2 weeks - 6 months, amounting to 74 people with 30 mininal samples using a simple random sampling technique. The results showed that the average milk production before the banana blossm consumption was 96.67 and after consuming the banana blosssom it increased to 108.00. The statistical test results are stated p value 0,000 (<α = 0.05), it can be concluded that Ha is accepted which means that there is a relationship of the banana blossom to the production of breast milk. Bananas Blossom can be used as a diet for breastfeeding mothers, which is beneficial to increase milk production.